Design and development of a prototype mobile manipulator - Zainul, Nur Saidah (2007)
This project is about the development of a mobile robot with manipulator arm for unloading purpose. The robot is designed to move from one location to another location that will move and unload an object to a preprogrammed location. The microcontroller PIC 16F877 is used for the control of the mobile manipulator. Two servo motors are placed at the manipulator ann to allow the robot to turn and twist. DC motors are used to move the robot from one location to another. The program or software use to control the movement of the mobile manipulator is developed using CCS Compiler for C-language. This research in robot technology can be applied in real life, as its task is to carry objects and unload them. As an example, it can be used to carry trash to the garbage bin. It can save cost for reducing human worker. Thus, the human worker can be relieved of the routine operation of this tedious task.